A Case of Adenosarcoma of the Uterus - Shigeki Taga; Mari Sawada; Aya Nagai; Dan Yamamoto; Ryoji Hayase (Hindawi Limited, 2014)
Adenosarcoma is a rare tumor which consists of benign glandular epithelium and malignant mesenchymal component. Here we report a case of adenosarcoma of the uterine corpus. Case Presentation. A 59-year-old woman presented with vaginal bleeding and visited a local clinic. She had a uterine tumor pointed out and was referred to our hospital. Ultrasound scans revealed a large heterogeneous mass occupying the whole uterine cavity. Cytological test of endometrium was performed but the result was negative. A fractional endometrial curettage revealed no malignancy. Magnetic resonance imaging (MRI) revealed a heterogeneous solid tumor of 77 × 76 mm. Total abdominal hysterectomy with bilateral salpingo-oophorectomy and pelvic lymphadenectomy was performed. On gross examination, the tumor was arising from the uterine body and occupied the whole uterine cavity. Histopathological examination revealed phyllodes-like architecture on low magnification　and　periglandular cuffing of tumor cells. The lesion was confined to the uterus. Histopathological final diagnosis was adenosarcoma. Her postoperative course was uneventful and she was discharged without postoperative treatment and remains alive without disease 6 months after the surgery.